Preparation and Characterization of Copolymeric Polymersomes for Protein Delivery - Nomani, Alireza; Nosrati, Hamed; Manjili, Hamidreza Kheiri; Khesalpour, Leila; Danafar, Hossein (Drug Research, 2017)
Biodegradable copolymeric polymersomes have been used for controlled drug delivery of proteins. These polymersomes important areas to overcome formulation associated problems of the proteins. The aim of this study was to develop polymersomes using biodegradable copolymers for delivery of bovine serum albumin (BSA) as a model protein. Encapsulated BSA by mPEG-PCL polymersomes led to formation of BSA-loaded mPEG-PCL polymersomes. The polymersomes synthesized with the protein-polymer ratio of 1:4 at 15 000 rpm gave maximum loading, minimum polydispersion with maximally sustained protein release pattern, among the prepared polymersomes. Investigation on FTIR and DSC results revealed that such a high encapsulation efficiency is due to strong interaction between BSA and the copolymer.The particles size and their morphology of polymersomes were determined by DLS and AFM.The encapsulation efficiency of BSA was 91.02%. The results of AFM showed that the polymersomes had spherical shapes with size of 49 nm.The sizes of BSA-loaded polymersomes ranged from 66.06 nm to 84.97 nm. The results showed that polymersomes exhibited a triphasic release, for BSA. Overall, the results indicated that mPEG–PCL polymersomes can be considered as a promising carrier for proteins.
Keywords: BSA; copolymers; sustained release; polymrsomes